Urgensi Pembelajaran Batasan Usia Pernikahan bagi Perempuan dalam Perspektif Hukum Islam: Studi Literatur tentang Perlindungan Hak dan Kesejahteraan - Mardliyati, Saadah (Berasan: Journal of Islamic Civil Law, 2024)
This study aims to examine the importance of learning the age limit of marriage for women from the perspective of Islamic law, by highlighting the implications for the protection of women's rights and family welfare. In Islamic law, marriage is not only a form of legalization of the relationship between a man and a woman, but also as an institution that aims to create a harmonious and prosperous domestic life. However, the age limit for marriage is often a matter of debate, especially in relation to aspects of health, education, and social welfare. This study uses a literature study method with a descriptive-qualitative approach, which analyzes various sources from fiqh books, Islamic legal regulations, and empirical research related to the impact of early marriage on women. Data is collected through literature review of journals, books, and relevant legal documents. The results of the study show that the age limit for marriage for women in Islamic law has flexibility, but still considers the aspects of maturity (rusyd) and benefits. These findings reveal that early marriage has a negative impact on women's reproductive health, education, and welfare, so there is a need for a deep understanding of the urgency of marriage age limits. In conclusion, learning about the age limit of marriage from the perspective of Islamic law is very important to increase public awareness and ensure that marriage is carried out in more ideal conditions and benefits for women and a more stable domestic life.